Use of time and adolescent health-related quality of life/wellbeing: A scoping review - Lycett, Kate; Wong, Monica; Wake, Melissa; Gold, Lisa; Olds, Tim (My University, 2017)
Time use could profoundly affect adolescents’ health-related quality of life (HRQL). Ideally, overall time use patterns would be considered, because activities within a 24-hour day are inherently correlated (more in one activity means less in another). This review focused on the associations of 1) overall time use patterns and 2) components of time use patterns with HRQL in adolescents. Conclusion: More physical activity, less screen time and more/adequate sleep, in isolation, are associated with better profile-based HRQL subscales. Greater understanding of adolescents’ overall time use patterns and HRQL is a priority for policy development.
Acta Paediatrica
Keywords: Health and wellbeing; Health and wellbeing